NCOG-23. PATIENT-REPORTED SYMPTOM BURDEN AND INTERFERENCE: A COMPARISON BETWEEN COVID-19 PANDEMIC YEAR AND NORMATIVE DATA IN PATIENTS WITH CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (12th November 2021) - Pillai, Valentina; Polskin, Lily; Vera, Elizabeth; Acquaye, Alvina; Briceno, Nicole; Choi, Anna; Christ, Alexa; Grajkowska, Ewa; Jammula, Varna; Leeper, Heather; Levine, Jason; Lindsley, Matthew; et al.
Abstract: CNS tumor patients are highly symptomatic causing interference with activity and worse quality of life. Social distancing due to the COVID-19 pandemic increased demands on the patient, caregivers, clinicians, and the health care system. The NCI's Neuro-Oncology Branch Natural History Study (NHS) systematically collected patient-reported outcomes (PROs) provide insight into how these challenges influenced symptom burden and interference during the COVID year. METHODS: Patient and disease characteristic as well as patient-reported symptoms and interference (MDASI-BT/-SP) and general health status (EQ-5D-3L) from 3/2020-2/2021) were compared to NHS normative sample collected prior to 3/2020. RESULTS: The sample (n = 178) was primarily White (82%), male (55%), median age of 45 (range 18 – 79) and KPS ³ 90 (51%). The majority had high-grade (70%) brain (83%) tumors (BT) with ≥ 1 prior recurrence (60%) and 25% were on active treatment. Clinical visits were primarily conducted via telehealth (64%) and 20% of all patients were diagnosed with progression at the time of assessment. Most commonly reported moderate-severe symptoms among BT patients were fatigue (30%), difficulty remembering (28%), feeling drowsy (22%). Among spinal cord tumor patients, fatigue (39%), pain (35%) and numbness/tingling in arms/legs/trunk (35%) were most frequently reported. These symptoms were reported in similar frequencies by the normative sample. Nearly half of the COVID year sample (48%) reported moderate-severe activity-related interference. Reported problems with mobility (38%), self-care (19%), pain/discomfort (40%), and usual activities (50%) were similar in both groups except for increased mood disturbance (53%) was reported during the COVID year. CONCLUSION: These findings support CNS tumor patients remained highly symptomatic with significant impact on health-related quality of life during the COVID year. Clinicians should develop timely individual care plans to help BT patients navigate their disease course. Evaluation of risk associated with more severe symptoms and functional limitations are ongoing.